Letter (copy) - Citrine, Walter, 1887-1983
027-0057-001 International. WMC/WJB/DT/85. 20th October, 1939. Senor Pascual Tomas, Depute 69, rue de Taur, Toulouse, FRANCE. Dear Senor Tomas, I duly received your letter of the 14th instant which from I gather that unfortunately the letter you sent to us on 30th August has got lost in the post. However, the enclosure was received and the matter proceeded with as soon as we recognised that it had come from you. I note the address you give and am communicating it at once to the Authorities for their guidance. Yours faithfully, General Secretary. 292/946/27/57